2022
DOI: 10.1007/s00170-022-09984-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on the explosive welding of niobium-steel

Abstract: The aim of this work is to study the use of explosive welding to produce Niobium-Steel composite plate, which is used in nuclear industry equipment material manufacturing. The welding parameters was determined by weldability window and numerical simulation was used to predict the wave shape of the welding interface. The morphology of the interface wave was observed by scanning electron microscope. Component measurement around interface waves. The experimental samples were investigeted using mechanical tests. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The results showed that the Nb-SS304 joining interface is featured by a wave structure with two vortices, and no obvious intermetallic compounds are formed at the joining interface. Wang and Li et al [16] performed explosive welding technologies on the joining of Nb and steel and found that the joining interface presented a waveform structure without no obvious defects. Among these welding technologies, the explosive welding technology shows excellent joining quality in the welding of Nb and other metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the Nb-SS304 joining interface is featured by a wave structure with two vortices, and no obvious intermetallic compounds are formed at the joining interface. Wang and Li et al [16] performed explosive welding technologies on the joining of Nb and steel and found that the joining interface presented a waveform structure without no obvious defects. Among these welding technologies, the explosive welding technology shows excellent joining quality in the welding of Nb and other metals.…”
Section: Introductionmentioning
confidence: 99%
“…In Xu et al's study [15], the Nb-SS304 explosive welded interface presents a waveform structure with two vortices and formed elongated and fine equiaxed grain structures near the interface. Wang and Li et al [16] found that the niobium-steel explosive welded interface presented a waveform structure without no obvious defects. The elemental analysis results indicated that a 5-µm diffusion layer was formed at the Nb-steel joining interface.…”
Section: Introductionmentioning
confidence: 99%